SMU Open House 2014 -- SMU Infographics - Singapore Management University (Institutional Knowledge at Singapore Management University, 2014)
Don't get lost in the urban jungle! Let this map help you plan your route during the SMU Open House 2014, happening on 1 and 2 March!